Ethnobotanical and ecological study of Punica granatum in Dir district, Khyber Pakhtunkhwa, Pakistan - K. Ali; S. Khan; N. Khan; W. Khan; I. U. Rahman; F. Ullah; K. Ali; M. Nisar (Regulatory Mechanisms in Biosystems, 2017)
Punica granatum L. (wild) belongs to family Punicaceae, a woody plant, predominantly found on calcareous and alkaline soils. The species is extensively utilized as food and firewood and for the extraction of various chemicals due to its therapeutic properties. To understand the ethno-botanical and ecological status of the species on a regional scale, a questionnaire survey was conducted in the Dir (L) area using close and open-ended questionnaires. Data collected from 124 respondents were analysed quantitatively using statistical analysis to calculate indices like Relative Frequency of Citation (RFC), Use value (UV) and multivariate analysis. GPS data used for the presence data of the plants were used to develop GIS thematic maps. Geo-referenced data on P. granatum was collected from the study area, using GPS. Results suggest that the plant is mostly used as a remedy for dry cough, as an astringent, people used powder form of fruit peelings. It was documented in the present investigation that P. granatum is mainly eradicated due to its extensive use as firewood. The study also evaluated on the major aspect of how the P. granatum can be conserved naturally. It was found out that the plant is conserved in areas inaccessible to humans. The status of the vegetation community around this plant was also explored, it is found out that specific shrub and tree communities were major flora growing in proximity to P. granatum. The finding of this survey has concluded that wild P. granatum is an endangered species due to its extensive and uncontrollable use for firewood, curing diseases and its economic potential. These findings could be exploited to take necessary steps for the conservation of this species.